Suppressing UAV payload swing with time-varying cable length through nonlinear coupling. (15th February 2023) - Huang, Jingwen; Tao, Hao; Wang, Yikun; Sun, Jian-Qiao
Abstract: This paper introduces a method to navigate the UAV flight and to suppress the payload swing by a nonlinear coupling control augmented with time-varying cable length. Special error signals are introduced that bring further coupling of dynamics among various states of the UAV and enable the flight control to effectively suppress the payload swing. The control is designed with the help of the dynamic model of the UAV in lift and transport operation. The stability of the control is proven in the Lyapunov sense. Extensive simulations and experiments have been carried out to demonstrate the effectiveness of the proposed nonlinear coupling control. Two popular control approaches in the literature are chosen to compare with the current work. It is found that the proposed control is quite effective in suppressing the payload swing while tracking the pre-determined path at the same time.